Implementasi Undang-Undang Nomor 13 Tahun 2003 dalam Perlindungan Hukum Karyawan CV. Husnajaya yang Dirumahkan Akibat Covid-19 - Aldilla Putri; Kalvin Aditia Brahmana; Andika Kristian Tarigan; Emir Syarif Fatahillah Pakpahan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This paper aims to determine the form of legal arrangements, agreements between workers legal responsibility and protection to workers based on the perspective of the Manpower Act. This study uses empirical juridical and data collected through field studies or observations and then analyzed qualitatively. This study concludes that the rule of law outside the employment contract and refers to the labor law that if the employer does not have the ability to pay in full, it is necessary to negotiate with the worker regarding the amount of wages, the method of payment and the length of time he is laid off. Meanwhile, for workers whose employment relationship is terminated, based on Article 164 paragraph (1) of Law Number 13 of 2003 concerning Manpower, the worker/labourer may be terminated by the employer on the grounds of force majeure, provided that the worker/laborer the person is entitled to severance pay in the amount of 1 (one) time under the provisions of Article 156 paragraph (2), a service award of 1 (one) time in the provisions of Article 156 paragraph (3) and compensation in accordance with the provisions of Article 156 paragraph (4). Thus, matters that regulate the working relationship between the company and workers have legal certainty and legal protection for workers as well as a form of responsibility for the company.